Age, sex and underlying heart rate as determinants of nocturnal heart rate variability among wearable smart ring users. (25th November 2020) - Kentta, T.V; Karsikas, M; Rantanen, A; Kinnunen, H; Koskimaki, H
Abstract: Background: Heart rate variability (HRV) is an important marker of overall health and especially cardiovascular health. Decreased HRV has been associated with reduced vagal control of heart rate and with adverse outcome in several studies. Purpose: The purpose of this study was to investigate the impact of demographic factors (age and sex) and underlying heart rate on nocturnal HRV among wearable smart ring users. Methods: De-identified data was gathered from 104, 431 wearable smart ring users over the course of one week (640, 911 nights; 65% men and 35% women; age 42.6±12.1 years). Inclusion criteria included self-reported age of ≥20 years and sleep duration ≥4 hours. The ring estimates heart rate and HRV with photoplethysmographic (PPG) sensors and calculates the root mean square of successive differences (rMSSD) between adjacent inter-beat-intervals (IBI) for 5-minute segments throughout each night. The average HRV in these segments was then taken to represent the cardiac parasympathetic activity among each user. In addition, rate-corrected HRV was calculated by dividing the rMSSD value with mean IBI (crMSSD = 100 * rMSSD/IBI). Results: Nocturnal HRV was significantly dependent on age and underlying heart rate (Figure). The observed rMSSD values declined with age (P<0.001) in both men and women. Concomitant decrease in rMSSD was observed with increasing heart rate in each age group (P<0.001). Statistically significant sex-related differences were observed in HRV. Men had higher crMSSD during the early decades of life (<40 years) than women. This difference diminished with age and women ≥50 years had higher crMSSD than their male coevals. The average resting heart rate decreased with age and was lower among men throughout the age groups (P<0.001). Conclusions: Normal aging is associated with reduced cardiac vagal modulation and is reflected as decreased nocturnal HRV values among male and female wearable smart ring users. The underlying heart rate is a significant factor for the degree of HRV throughout life. In this population, the sex-related differences observed during the early decades of life diminish on the verge of midlife and are reversed later in life with women showing higher HRV during and after midlife. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Oura Health Ltd